Heritability, genetic variability and genetic gain for yield and morphologic characters in young progenies of rubber trees - Boock, Marcello Villar; Gonçalves, Paulo de Souza; Bortoletto, Nelson; Martins, Antonio Lúcio Mello (Pesquisa Agropecuaria Brasileira, 1995)
The objective of this paper was to estimate inheritance for yield and morphologic characters in three-year old progenies of rubber trees [Hevea brasiliensis (Willd ex Adr. de Juss) Müell Arg]. Twenty-two half-sib progenies of rubber tree were planted at the randomized complete block design. The characters studied were: yield, girth; leaf petiole length; leaf petiole diameter; leaf petiole index; main venation length; main venation diameter; foliar width and leaf area. Heritability and genetic gain were estimated for those characters. The results indicated significative differences for most of the characters. The individual heritability estimates were higher values for girth, main venation length and yield with values of 0,47; 0,45 and 0,35, respectively. The genetic gain estimates among and within the progenies showed considerable values of 49,09%; 21,44% and 18,42% for yield, leaf area and girth, respectivelly.